Konsep Fasakh Dalam Nikah Karena Ada Cacat Perspektif Hukum Islam - Nilpa Safitri Daulay (Jurnal Budi Pekerti Agama Islam, 2024)
This research aims to determine defects in marriage from an Islamic legal perspective. And to understand the concept of marriage fasakh due to a flawed Islamic legal perspective. This research was carried out using library research and paying attention to the field (Field Research). The results of the research show that defects in marriage from an Islamic legal perspective are physical and spiritual defects that cannot be removed or can be removed but only in a long time. Among the diseases specific to men: (1) Jabb/castration, namely cutting off the genitals (penis) and both testicles. (2) Unnah/impotence. (3) Khusha', namely cutting, finding or removing both testicles, without cutting the penis. And defects specifically for women are (1) Ratq, namely blockage of the vaginal canal, (2) Qarn, namely the presence of something that protrudes and blocks the vaginal canal. (3) 'afal, namely the appearance of foam in the vagina. (4) Ifdha, namely the mixing of the sexual canal with the urinary tract, or the mixing of the sexual canal with the anal canal. (5) Istihadhah. The defects that exist in men and women are (1) madness, (2) Leprosy (juzam). (3) Leprosy (baras), (4) Bakhar disease (foul-smelling mouth) and Sunan (foul-smelling sweat. And Imam Ahmad made transvestism a defect which causes marriage fasakh. The concept of marriage fasakh is caused by a defect in the perspective of Islamic law, which is to sever ties of relationship. between husband and wife. This occurs because the conditions are not fulfilled when the marriage contract takes place. In the Hanafi and Maliki schools of thought, this divorce is categorized as thalak ba'in and cannot be reconciled, and according to the Syafi'i and Hanbali schools it is stated that separation between the husband and a wife who is caused by an illness or defect is called fasakh, not thalak (divorce carried out by the husband). And if the defect is known before marrying her, he may divorce her and he is not obliged to pay the dowry.